Bioethylene Production from Ethanol: A Review and Techno‐economical Evaluation. Issue 2 (31st March 2017) - Mohsenzadeh, Abas; Zamani, Akram; Taherzadeh, Mohammad J.
Abstract: Manufacturing of bioethylene via dehydration of bioethanol is an alternative to the fossil‐based ethylene production and decreases the environmental consequences for this chemical commodity. A few industrial plants that utilize 1st generation bioethanol for the bioethylene production already exist, although not functioning without subsidiaries. However, there is still no process producing ethylene from 2nd generation bioethanol. This study is divided into two parts. Different ethanol and ethylene production methods, the process specifications and current technologies are briefly discussed in the first part. In the second part, a techno‐economic analysis of a bioethylene plant was performed using Aspen® plus and Aspen Process Economic Analyzer, where different qualities of ethanol were considered. The results show that impurities in the ethanol feed have no significant effect on the quality of the produced polymer‐grade bioethylene. The capacity of the ethylene storage tank significantly affects the capital costs of the process. Abstract : Bioethylene production from bioethanol is considered an alternative to the fossil‐based route. Although processes for the use of 1st generation bioethanol already exist, 2nd generation bioethanol has so far not been covered. This review summarizes different production methods and analyses the effects of impurities in the ethanol as well as the storage tank capacities on the overall process costs.